The Semiotics of Emotions in Diwan (wtar unajy kawsah) By Maher's Mahl Alrehaily - Alfawaz, Alreem Mufwaz; Elgheity, Mrwa Mokhtar (Journal of Arabic Language Sciences and Literature, 2023)
The semiotic theory of emotions is concerned with the study of the emotions of the self while it works, deriving its principles from the semiotics of action, where emotions and passions are an essential part of the human being. Saudi Arabian poetry has kept up with its quality and creativity Arabic texts, and the poetic output of Al-Rahili was the best representative of that, therefore, the researcher chose a diwan (wtar unajy kawsah), as it carries conscious depth and ambiguity, because passions and emotional states are strongly stated in it, The problem of the study was the emergence of passions and emotional tensions that abounded in the Diwan; therefore, the study sought to achieve a critical vision of it in poetic discourse, and relied on the semiotics of emotions, and applied its procedures according to the theory of Grimas and Jacques Fontenay in their book (Semiotics of Emotions). Through the discovery of the characteristics of emotions and their representations, and monitoring of the path of the formation of the value system of emotions, the results of the study summarized in the diversity of what was included in the Diwan from emotions whose effects appeared in the poetic discourse.The emotions have drawn the features of the self-personality to introduce us to a model of the optimism emotions. In pursuit of human development and qualify life in presence of crises, The study recommends intensifying critical efforts on the semiotics of emotions; To form the features of Arab values.
Keywords: modern literary criticism; contemporary Saudi poetry; semiotics of passions; Maher Al-Ruhaili